Development of Visual-Moving Thinking of Students (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
this article reflects on the development of visual-action thinking by readers. At the same time, the defining feature of the form of thinking, the inherent advantage of visual-moving thinking are illuminated.